The Relationship Between Foreign Aid and Governance Performance in Nepal: Evidence from Worldwide Governance Indicators (2003–2023) (Pragyaratna प्रज्ञारत्न, 2025)
Despite substantial foreign aid inflows over the past decades, governance outcomes in many developing countries remain mixed and not well understood. Nepal, a major aid recipient undergoing significant political transitions, provides a useful case to examine this paradox. This study examines the relationship between foreign aid and governance performance in Nepal from 2003 to 2023, focusing on six key indicators: government effectiveness, control of corruption, rule of law, Political Stability & Absence of Violence/Terrorism, Regulatory Quality and Voice and Accountability. Using the Worldwide Governance Indicators (WGI) dataset prepared by World Bank, the study employs time series analysis and Pearson correlation analysis alongside descriptive trend examination to quantify relationships between aid and governance indicators. The findings reveal a moderate negative correlation between aid and rule of law (r = -0.45, p < 0.05), while government effectiveness and control of corruption show no significant positive relationships with aid inflows. Time series decomposition further confirms that despite increased aid, Nepal’s governance scores experienced little or no sustained improvement, especially during periods of high aid inflows (2010–2015). This challenges assumptions about the transformative potential of aid and highlights constraints caused by weak institutional capacity and unsettled political situations. This study’s use of WGI helps address previous methodological gaps in Nepal-focused governance research, though it also recognizes limitations due to the perception-based and aggregated nature of the data. These insights have important implications for donors and policymakers, emphasizing the need for aid strategies that are politically informed and aligned with local institutional realities. The paper recommends future research on subnational governance and varied aid approaches during Nepal’s ongoing federal transition.